Characteristics, properties and morphology of calcium silicate nanoparticles modified with some silane coupling agents - Nguyen Anh Hiep,; Nguyen Thuy Chinh,; Mai Duc Huynh,; Dao Phi Hung,; Phung Thi Lan,; Nguyen Tien Dung,; Nguyen Thi Nga,; Thai Hoang, (Vietnam Journal of Science and Technology, 2022)
This paper presents the characteristics, properties and morphology of calcium silicate (CS) nanoparticles modified with silane coupling agents, namely vinyltrimetoxy silane (VTMS) and 3-(trimethoxysilyl)propyl methacrylate silane (MPTS), by the hydrolysis method. Effect of content of silane coupling agents on CS nanoparticles modified was investigated. The obtained results suggested that silane coupling agents were successfully grafted onto the surface of CS nanoparticles. The performance and amount of silane coupling agent grafting on CS nanoparticles depended on the nature and initial content of silane coupling agent. The highest grafting yield on CS nanoparticles performances was 32.8 % for VTMS at initial content of 5 wt. % and 48.80% for MPTS at initial content of 10 wt. %. Organo-modification decreased thermo-oxidation stability of modified CS nanoparticles because of the decomposition of organic moiety in silane coupling agent while hydrophobicity of modified CS surface increased. Thus, agglomeration of modified CS nanoparticles reduced significantly. The unmodified CS nanoparticles had size distribution (in distilled water) peak at nearly 500 nm while the size distribution (in distilled water) peak of CS modified 10 wt.% MPTS was approximately 150nm.